(untitled) (Trabalho & Educação, 2018)
This article discusses the historical course of training in-service of health workers in Brazil from the official documents published. The objective of this study was to trace the historical trajectory of the training that occurs in the work environment of workers in the field of health in Brazil, in order to understand the historical process that resulted in the so-called Permanent Health Education (EPS) - in-service training policy adopted in the country for health workers from the beginning of the 2000s. It was observed with this analysis that the training of the health worker went through three distinct historical moments: the first period was characterized by a slight formation between the 1960s and 1980s, since during this period there were shortages of health workers of various professional categories with formal training and the health demands of the populations were increasing with the development of the country; the second moment, after the 1980s, even after the creation of the Sistema Único de Saúde (SUS), the training of health workers still met the demands of the developing market, with increasing specialization of the professions, skills and competences, but with little adherence to the needs of health workers and populations; and the third, the work and work training required and guided by the National Policy on Permanent Education in Health (PNEPS), where training must take place according to the real needs of real workers in action, improve the health of populations. ___ Este artigo aborda o percurso histórico da formação em serviço dos trabalhadores da saúde no Brasil a partir dos documentos oficiais publicados. Objetivou-se traçar o percurso histórico da formação que ocorre no ambiente de trabalho dos trabalhadores no campo da saúde no Brasil, a fim de entender o processo histórico que resultou na chamada Educação Permanente em Saúde (EPS) – política de formação em serviço adotada no país para os trabalhadores e trabalhadoras da saúde a partir do início dos anos 2000. Observou-se, com esta análise, que a formação do trabalhador da saúde passou por três momentos históricos distintos: o primeiro momento se caracterizou por uma formação aligeirada entre as décadas de 1960 e 1980, pois nesse período havia escassez de trabalhadores da saúde de várias categorias profissionais com formação formal e as demandas de saúde das populações eram crescentes com o desenvolvimento do país; o segundo momento, após a década de 1980, mesmo após a criação do Sistema Único de Saúde (SUS), a formação dos trabalhadores da saúde ainda atendia às demandas do mercado em desenvolvimento, com crescente especialização das profissões, formação de habilidades e competências, porém, com pouca adesão às necessidades dos trabalhadores da saúde e das populações; e o terceiro momento, a formação no trabalho, pelo trabalho e para o trabalho, requerida e orientada pela Política Nacional de Educação Permanente em Saúde (PNEPS), em que a formação deve ocorrer de acordo com as necessidades reais de trabalhadores reais em ação, a fim de melhorar a saúde das populações.